Impact of COVID-19 Lockdowns on Sexual Health Care Utilization and STD Reporting, Maricopa County. (1st November 2021) - Bell, Jonathan; Canepa, Stefano; Kreis, Stephanie; Taylor, Melanie M.
The Maricopa County Department of Public Health (MCDPH) Sexually Transmitted Disease (STD) Clinic remained operational during a 6-week statewide Coronavirus Disease 2019 (COVID-19) Stay-at-Home Order. The present study sought to evaluate the effect of the Stay-at-Home Order on countywide STD reporting and uptake of sexual health services. We compared countywide daily median STD reporting and MCDPH STD clinic attendance across 3 timeframes; (1) Pre-Lockdown (01/01/2020–03/30/2020); (2) Lockdown (03/31/2020–05/15/2020); and (3) Post-Lockdown (05/16/2020–12/31/2020). STD reporting was characterized as incident chlamydia, gonorrhea, and primary and secondary syphilis. Clinic attendance was characterized as clients visiting through express testing or provider visits. Differences in STD reporting and clinic attendance were evaluated using non-parametric testing. Comparing Pre-Lockdown to Lockdown, we observed significant declines in the daily median chlamydia case reporting (−22%) and clinic express testing attendance (−29%). Comparing Lockdown to Post-Lockdown, we observed significant increases in daily median chlamydia and gonorrhea case reporting (+20%, +15%; respectively) and clinic express testing and provider visits (+42%, +20%; respectively). No significant difference was observed in countywide syphilis reporting across the 3 timeframes. Declines in STD reporting were observed countywide during the lockdown and were concurrent with declines in attendance observed at the MCDPH STD Clinic. Maintenance of clinic operations during the lockdown allowed for continued uptake of STD testing, diagnosis, treatment, and partner services. This study of sexual health care utilization at the public STD clinic in Maricopa County, Arizona, found reduced testing and provider visits contributed to lower countywide STD reporting during the Arizona COVID-19 Stay-at-Home Order.